New species of the genus Navicula Bory (Bacillariophyceae, Naviculaceae) from Lake Teletskoye - Chudaev, Dmitry A. (Phytotaxa, 2019)
A new species from the diatom genus Navicula—N. teletskoyensis sp. nov. is described from mountain oligotrophic Lake Teletskoye (West Siberia). Morphology of the taxon was studied under light and scanning electron microscopy. New species is compared with morphologically similar species, it resembles N. pseudolanceolata, N. bourrellyivera, N. trivialis, N. oligotraphenta, N. hanseatica, N. melovskii, N. subconcentrica, N. johncarteri and N. vaneei.